Exploring the horizon of High-End Fashion amongst Gen Z in India - Verma, Kanika (2024)
This thesis aims to understand the attitudes and perceptions of the Generation Z segment in India on how they perceive high-end fashion, what importance it holds for them, and the motivating factors driving their actions to purchase fashion goods. This study focuses on the influential factors responsible for shaping the brand perceptions of Indian Gen Z. The study further delves into the theoretical portion, which provides a deeper understanding of relevant concepts in the Indian fashion industry to understand better the cohort’s inclination towards luxury fashion. To attain the objective of this thesis, a qualitative approach was used, which included individual interviews with Generation Z consumers from India to understand and analyze their attitudes towards high-end fashion. Findings revealed that attitudes and motivations relating to high-end luxury purchases vary among individuals with an emphasis on four main attributes ‘Quality, Usability, Status symbol, and durability’ of luxury goods. Despite the financial constraints, Gen Z shows a positive perception and attitude towards luxury brands. With increased earning capacity, the intention to purchase these goods will rise. Luxury brands can benefit from these insights, implying strategies based on the consumers’ perceptions, understanding the potential challenges, and adapting their marketing strategies accordingly to cater to the cohort, meeting their demands.